2020
DOI: 10.1002/csc2.20267
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of different strategies for building training sets for genomic predictions in segregating soybean populations

Abstract: The design of the training set is a key factor in the success of the genomic selection approach. The nature of line inclusion in soybean [Sorghum bicolor (L.) Moench.] breeding programs is highly dynamic, so generating a training set that endures across the years and regions is challenging. Therefore, we aimed to define the best strategies for building training sets to apply genomic selection in segregating soybean populations for traits with different genetic architectures. We used two datasets for grain yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As well, adding the interaction effect G × W (M5) increases PA when compared to the main effects models (M1 and M3), but not as much as models containing the G × E, similar to what was already presented by Robert et al (2020) and Jarquin et al (2021); however, G × W has the advantage of predicting new environments (Costa-Neto et al, 2021a;Jarquin et al, 2021;Robert et al, 2020), which has not been tested here. Also, MTMET models gave a small increase in PA compared with STMET, especially for models containing the G × E term (Lyra et al, 2017;Mendonça & Fritsche-Neto, 2020). Furthermore, as Costa-Neto et al (2021a) reported, including the W matrix helps increase PA, especially in the case of untested hybrids and/or untested environments, by better explaining sources of variation, capturing the environment potential per se and its interaction with the genotypes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As well, adding the interaction effect G × W (M5) increases PA when compared to the main effects models (M1 and M3), but not as much as models containing the G × E, similar to what was already presented by Robert et al (2020) and Jarquin et al (2021); however, G × W has the advantage of predicting new environments (Costa-Neto et al, 2021a;Jarquin et al, 2021;Robert et al, 2020), which has not been tested here. Also, MTMET models gave a small increase in PA compared with STMET, especially for models containing the G × E term (Lyra et al, 2017;Mendonça & Fritsche-Neto, 2020). Furthermore, as Costa-Neto et al (2021a) reported, including the W matrix helps increase PA, especially in the case of untested hybrids and/or untested environments, by better explaining sources of variation, capturing the environment potential per se and its interaction with the genotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, LA-GA-T optimizes the selection, on a genetic basis, of the n genotypes informed by APY to compose our optimized training set (OTS) (Fristche-Neto et al, 2018). In this context, Mendonça & Fritsche-Neto (2020) used the algorithm designed by Akdemir (2017) to select the most representative genotypes to build the training population. Similar to our findings, they did not notice an increase in PA while using OTS, but reduced the budget.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the W matrix can optimize complex information, as we saw in our OTS’ scenarios, and optimize trials [ 25 ]. Also, MTMET models showed a small PA increase compared with STMET, especially for models containing the G × E term [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LA-GA-T optimizes the selection, on a genetic basis, of the n genotypes informed by APY to compose our optimized training set (OTS) [ 18 ]. In this context, Mendonça and Fritsche-Neto [ 35 ] used the algorithm designed by Akdemir [ 2 ] to select the most representative genotypes to build a training population. Similar to our findings, they did not notice an increase in PA while using OTS but were able to reduce the budget.…”
Section: Discussionmentioning
confidence: 99%
“…As well, add the interaction effect G × W (M5) increases PA when compared to the main effects models (M1 and M3), but not as much as models containing the G × E, similar to what was already presented by Robert et al (2020) and (Jarquin et al, 2021), however, G × W has the advantage of predicting new environments Jarquin et al, 2021;Robert et al, 2020), that has not been tested here. Also, MTMET models gave a small increase in PA compared with STMET, especially for models containing the G × E term (Lyra et al, 2017;Mendonça & Fritsche-Neto, 2020). Furthermore, as Costa-Neto et al (2021a) reported, including the W matrix helps increase PA, especially in the case of untested hybrids and/or untested environments, by better explaining sources of variation, capturing the environment potential per se and its interaction with the genotypes.…”
Section: Discussionmentioning
confidence: 93%